2005
DOI: 10.1002/pd.1207
|View full text |Cite
|
Sign up to set email alerts
|

Second trimester ultrasound prenasal thickness combined with nasal bone length: a new method of Down syndrome screening

Abstract: In the second trimester, PT is increased on average in DS fetuses. Combining PT and NB measurement could yield a higher screening detection rate than NB alone. Confirmation of our findings in a series of women scanned before the karyotype was known is needed before the method can be clinically implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
86
6
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(112 citation statements)
references
References 28 publications
9
86
6
1
Order By: Relevance
“…These results are compatible with those of previous studies [1,2,3,4,5,6,7] and suggest that measurement of the PFSR may provide an effective method of screening for trisomy-21 in the second-trimester of pregnancy.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These results are compatible with those of previous studies [1,2,3,4,5,6,7] and suggest that measurement of the PFSR may provide an effective method of screening for trisomy-21 in the second-trimester of pregnancy.…”
Section: Discussionsupporting
confidence: 82%
“…Two previous studies that specifically examined prenasal thickness reported similar median values in normal fetuses of 2.4 mm at 16 weeks and about 4.5 mm at 24 weeks and in fetuses with trisomy-21 at 16-24 weeks the values were above the 95th percentile in 72% of 18 and 73% of 26 cases, respectively [1,2]. …”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Short nasal bone length (NBL), increased prenasal thickness (PT), and increased nuchal fold thickness (NF) are the most frequently investigated [1,2,3,4,5,6,7,8,9,10,11,12]. Recent studies have indicated that the use of ratios, such as the prenasal thickness to nasal bone length ratio (PT-NBL ratio) and the prefrontal space ratio (PFSR), are strong and easy-to-use second-trimester markers [13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The latest screening strategy for first and second trimester was introduced by Nicolaides et al ( 51,53,60,65,69,70,[74][75][76][77][78][79][80][81][82][83] CRL, BPD, FHR and FL were measured from the beginning of the obstetric ultrasound era.…”
Section: The Explanation Of the Resultsmentioning
confidence: 99%